2015
DOI: 10.3126/hprospect.v14i1.12369
|View full text |Cite
|
Sign up to set email alerts
|

Types of cooking stove and risk of Acute Lower Respiratory Infection among under-five children: a cross sectional study in Rasuwa, a Himalayan district of Nepal

Abstract: Background:In Nepal, about 75% people rely on wood and other biomass fuels for cooking. The majority of Nepali families cook on a traditional stove, an open fire in the kitchen resulting in indoor air pollution, one of the key risk factors for Acute Lower Respiratory Infection (ALRI) among under-five children.The study aimed at exploring the association of indoor air pollution due to use of traditional cooking stoves with ALRI among under-five children in Rasuwa, a Himalayan district of Nepal. Methods:A cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…This review showed that children from the household who used charcoal and main house for a place of cooking were more than two times more likely to develop pneumonia than those who did not use it. This finding was supported by other studies [22,37,38]. The possible explanations could be high indoor air pollution may adversely affect host defenses of the respiratory tract against pathogens.…”
Section: Discussionsupporting
confidence: 88%
“…This review showed that children from the household who used charcoal and main house for a place of cooking were more than two times more likely to develop pneumonia than those who did not use it. This finding was supported by other studies [22,37,38]. The possible explanations could be high indoor air pollution may adversely affect host defenses of the respiratory tract against pathogens.…”
Section: Discussionsupporting
confidence: 88%
“…is review showed that children from the household who used charcoal and main house for a place of cooking were more than two times more likely to develop pneumonia than those who did not use it. is finding was supported by other studies [21,37,38]. e possible explanations could be high indoor air pollution may adversely affect host defenses of the respiratory tract against Journal of Environmental and Public Health pathogens.…”
Section: Discussionsupporting
confidence: 77%
“…Exposures to biomass fuels are associated with many respiratory diseases such as acute respiratory infections, chronic obstructive pulmonary disease, lung cancer, pulmonary tuberculosis, and asthma [ 7 ]. Exposure to biomass fuel smoke from a traditional stove is one of the factors leading to acute respiratory infections among under-five children [ 8 ]. Acute respiratory infection is the most common causes of under-five illness and mortality that account for 94,037,000 disability adjusted life years and 2 million deaths worldwide [ 1 ].…”
Section: Introductionmentioning
confidence: 99%